“It’s about Human Connection”: Transgender Community Wisdom to Inform Practice - Huezo, Mateo; Collins, Sandra (Canadian Journal of Counselling and Psychotherapy, 2019)
Therapists in Canada are expected to address mental health disparities, but they receive little education or institutional support for ethical practices with transgender (or trans) clients. Across the literature, authors have highlighted the importance of connecting with trans communities for trans-affirmative care. However, with a general lack of information about these communities, professionals are not set up for success. In this paper we describe a community-based participatory research study with 12 participants, designed to look at the challenges, strengths, and characteristics of transgender communities in Alberta. We discuss the implications of this work towards anti-oppressive, trans-centred research and care.